THE RELATIONSHIP BETWEEN NUTRITIONAL STATUS AND GLUCOSE TOLERANCE IN PREGNANCY - Merve Yabacı; Cemile İdiz; Bedia Fulya Çalıkoğlu; Atıl Yüksel; Beyhan Ömer; Birsen Demirel; Emel Özer; İlhan Satman (İstanbul Tıp Fakültesi Dergisi)
Objective: Gestational diabetes mellitus (GDM) is a form of diabetes that appears during pregnancy and can cause both maternal and fetal consequences if left untreated. The aim of this study was to investigate the relationship between the nutritional characteristics of pregnancy and the development of GDM and gestational glucose intolerance (GGIT). Material and Method: Three groups of pregnant women were included in the study. They were grouped according to the results of the oral glucose tolerance test (OGTT-50 g and 100 g) as follows: normal glucose tolerance (NGT, n=60), GGIT (n=60), and GDM (n=60). The demographic characteristics, health conditions, and nutritional habits of the participants were questioned, and a 3-day food consumption record was requested from the patients. Results: Average age, body weight, daily carbohydrate and protein intakes, and the frequency of diabetes history in the family were found to be higher in the GDM and GGIT groups than in the NGT group. It was also found that the amount of fat intake was higher in the GDM group than in the NGT and GGIT groups (p<0.05). According to logistic regression models, age, daily protein, carbohydrate, and fat consumption, not being pregnant before, and having a body mass index (BMI)>25 kg/m2 before pregnancy were the factors associated with the risk of GDM. Similarly, age, daily protein consumption, having a macrosomic baby, and current smoking were positively associated with the risk of GGIT. Conclusion: The phenotypic characteristics, family history of diabetes, and previous obstetric problems in pregnant women were found to be closely related to GDM or GGIT risk. Special attention should be paid to general health and balanced nutrition, especially in high-risk pregnant women.